Acquisition of telicity in L2: A psycholinguistic study of Japanese learners of English - Kaku, Keiko (University of Ottawa (Canada), 2009)
This dissertation investigates the acquisition of the semantics of telicity by Japanese learners of English with emphasis on a particular grammatical phenomenon, the neutral perfective reading of simple past predicates (Singh, 1991), which is available in Japanese but not in English. Three main points are of interest in this dissertation: First, we examine whether or not Japanese learners of English learn to derive the telicity of a simple past predicate despite lack of explicit classroom instruction. Second, we investigate potential factors that may assist L2 learners in discovering a target-like representation of the predicate telicity in English. Finally, we aim at revealing the L2 learners' developmental profile for the acquisition of the semantics of telicity. Two experimental tasks, a morphological task and a truth-value judgment task, were conducted which included three proficiency levels of L2 learners (beginner, intermediate and advanced), as well as native speakers of English and Japanese. Empirical data from the experimental tasks indicated that Japanese learners of English succeeded in progressing towards target-like representation of telicity. While the beginners directly transferred the L1 Japanese representation of the semantics of predicate telicity onto their target language, the intermediate and advanced levels dissociated the telicity of the English simple past predicates from that of the Japanese past predicates. That is, they learned to invalidate the neutral perfective reading of English predicates. We postulate that L2 learners' progress in the acquisition of the semantics of English predicate telicity can be accounted for by the acquisition of Det/Num morphology and by a Bayesian learning model: This learning model helps learners use L2 input to make form-meaning inferences on the predicate telicity and aids them to gradually acquire the most appropriate representation of English predicate telicity.
Keywords: Language, Linguistics.; Education, English as a Second Language.